ANALISIS PENGARUH ROTASI PEKERJAAN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada CV Sempurna Boga Makmur Semarang) - Setiawan, Andi (JURNAL BISNIS STRATEGI, 2011)
This study aimed to test the effect of job rotation on the performance of employees with the motivation to work as an intervening variable. According to the results of previous studies, job rotation is part of the design program of work focused on designing the work to create a way in which employees can work without getting bored because of doing certain repetitive jobs. Job rotation will create a diversity of tasks for employees so as to motivate them to work better.The research was conducted at the company's CV Sempurna Boga Makmur Semarang. The number of samples examined in this study were 63 employees of CV Sempurna Boga Makmur that had already been rotated, and data collection methods used by distributing questionnaires. The collected data were then analyzed using path analysis method. The analysis shows that job rotation does not affect the work motivation, job motivation gives positive and significant impact on the performance of employees, job rotation gwes positive and significant impact on employee's performance.Based on the analysis, then the managerial implications that can be associated with an increase in the employee's performance is to prepare employees so they can perform a good job rotations, providing direction for the employee to feel happy in their work and lead their interest to better work, and provide direct demonstration so that employees can understand clearly about the explanation.